Adrenal lipoma formation via PI(3,4,5)P 3 /AKT-dependent transdifferentiation of adrenocortical cells into adipocytes - Shogo Yanai; Junko Sasaki; Hyeon-Cheol Lee-Okada; Fumiya Takahashi; Yuto Kikuchi; Shin Morioka; Toshiyoshi Yamamoto; Katsuya Yuguchi; Miko Oikawa; Hiroaki Kajiho; Takashi Baba; Chikako Yokoyama; et al. (Proceedings of the National Academy of Sciences, 2025)
Adrenal lipomas are benign tumors containing ectopic adipose tissue in the adrenal gland, an organ that normally lacks both adipocytes and their progenitors. The origin of this ectopic fat remains enigmatic, and the absence of a genetic animal model has hindered its investigation. Phosphatidylinositol 3,4,5-trisphosphate [PI(3,4,5)P 3 ], a key signaling lipid that regulates cellular growth and differentiation, is tightly regulated by the lipid phosphatases PTEN (phosphatase and tensin homolog) and SHIP2 (SH2-containing inositol phosphatase 2). Here, we demonstrate that simultaneous loss of Pten and Ship2 in the adrenal cortex induces adrenal lipoma formation in mice. These lipomatous cells display both adipocyte-like morphology and adipocyte-specific gene expression. Lineage tracing revealed that these lipomas originate from the adrenal cortex. Mechanistically, PI(3,4,5)P 3 hyperaccumulation in the adrenal cortex activates AKT (AKT8 virus oncogene cellular homolog), leading to ectopic PPARγ (peroxisome proliferator activated receptor gamma) expression, a key driver of adipocyte differentiation. This study suggests that the PI(3,4,5)P 3 /AKT-driven transdifferentiation of adrenocortical cells may represent a central mechanism underlying adrenal lipoma formation, thereby providing insights into lipoma pathogenesis and cellular reprogramming in vivo.